Odpowiedzi

Najlepsza Odpowiedź!
2010-01-06T20:00:21+01:00
A)
x=-y
x-y=6

x=-y
x-y-y=6

x=-y
x-2y=6/:(-2)

x=-y
x/2+y=3

b)
y=x+3
2x+y=9

y=x+3
2x+x+3=9

y=x+3
3x=9-3

y=x+3
3x=6/:3

y=x+3
x=2

x=2
y=2+3=5

c)
x-4y=15
y=4x

y=4x
x-4*(4x)=15

y=4x
x-16x=15

y=4x
-15x=15/:(-15)

y=4x
x=-1

x=-1
y=4

d)
y=-2x-1
x=y+7

x=y+7
y=-2*(y+7)-1

x=y+7
y=-2y-14-1

x=y+7
y+2y=-15

x=y+7
3y=-15/:3

y=-5
x=-5+7

y=-5
x=2

e)
-3x=2y
y=1-x

y=1-x
-3x=2*(1-x)

y=1-x
-3x=2-2x

y=1-x
-3x+2x=2

y=1-x
-x=2/*(-1)

x=-2
y=1-2

x=-2
y=-1
2010-01-06T20:15:39+01:00
A)
x=-y
x-y=6

x=-y
-y-y=6

x=-y
-2y=6 / :-2

x=-y
y=-3
x=-(-3)= 3

b)
y=x+3
2x+y=9

y=x+3
2x+x+3=9

y=x+3
3x+3=9

y=x+3
3x=9-3

y=x+3
3x=6 /:3

y=x+3
x=2
y=2+3=5

c)
x-4y=15
y=4x

x-4(4x)=15
y=4x

x-16x=15
y=4x

-15x=15
y=4x

x=-1
y=4*(-1)=-4

d)
y=-2x-1
x=y+7

y+2x=-1
x=y+7

y+2(y+7)= -1
x=y+7

y+2y+14= -1
x=y+7

3y= -14-1
x=y+7

3y= -15 / :3
x=y+7

y=-5
x= -5-7=2

e)
-3x=2y
y=1-x

-3x-2y=0
y=1-x

-3x-2(1-x)=0
y=1-x

-3x-2+2x=0
y=1-x

-x=2
y=1-x

x=-2
y=1-2=-1

f)
5x+6x=8
x=4y-1 -----> ten przyklad raczej zle jest napisany















2010-01-06T20:21:20+01:00
A)
x= -y
x - y =6
x= -y
-y -y =6
x= -y
-2y= 6/:(-2)
x= -y
y= -3
x= 3
y= -3

b)
y=x+3
2x+y=9
y=x+3
2x+x+3=9
y=x+3
3x=6/:3
y=x+3
x=2
y=2+3
x=2
y=5

c)
x-4y=15
y=4x
x-16x=15
y=4x
-15x=15/:(-1)
y=4x
x=-1
y=4*(-1)
x=-1
y=-4

d)
y=-2x-1
x=y+7
y=-2x-1
x=-2x-1+7
y=-2x-1
3x=6/:3
y=-2x-1
x=2
y=-5

e)
-3x=2y
y=1-x
-3x=2(1-x)
y=1-x
-3x=2-2x
y=1-x
-x=2/:(-1)
y=1-x
x=-2
y=1+2
x=-2
y=3